Catecholamine-induced vasoconstriction is sensitive to carbonic anhydrase I activation - Puscas,I. (2001)
We studied the relationship between alpha- and beta-adrenergic agonists and the activity of carbonic anhydrase I and II in erythrocyte, clinical and vessel studies. Kinetic studies were performed. Adrenergic agonists increased erythrocyte carbonic anhydrase as follows: adrenaline by 75%, noradrenaline by 68%, isoprenaline by 55%, and orciprenaline by 62%. The kinetic data indicated a non-competitive mechanism of action. In clinical studies carbonic anhydrase I from erythrocytes increased by 87% after noradrenaline administration, by 71% after orciprenaline and by 82% after isoprenaline. The increase in carbonic anhydrase I paralleled the increase in blood pressure. Similar results were obtained in vessel studies on piglet vascular smooth muscle. We believe that adrenergic agonists may have a dual mechanism of action: the first one consists of a catecholamine action on its receptor with the formation of a stimulus-receptor complex. The second mechanism proposed completes the first one. By this second component of the mechanism, the same stimulus directly acts on the carbonic anhydrase I isozyme (that might be functionally coupled with adrenergic receptors), so that its activation ensures an adequate pH for stimulus-receptor coupling for signal transduction into the cell, resulting in vasoconstriction.